Launch of Abby and friends ATI adventure - Access to Information Unit Office of the Prime Minister
This programme was done for the launch of Abby and Friends ATI Adventure. It was put on by the Access to Information Unit in the Office of the Prime Minister. The launch took place at the Kingston and St. Andrew Parish Library on March 26, 2018. A reading of an excerpt from the book was done by the Honourable Floyd Green, then Minister of State.
Keywords: Programme. -- Jamaica